2009
DOI: 10.1097/ccm.0b013e3181a005ba
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine attenuates tubular cell apoptosis in acute kidney injury via inhibition of the c-Jun N-terminal kinase phosphorylation of 14-3-3*

Abstract: A signaling link between JNK and 14-3-3 and subsequent mitochondrial death pathway may partly act as an early signaling that promotes apoptotic cell death leading to AKI, and glutamine may at least partially prevent apoptosis via enhancing Hsp70 or GSH levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 70 publications
1
38
0
Order By: Relevance
“…Low serum prealbumin levels, a marker of nutritional status, were correlated with increased mortality in adults with AKI (44), and sustained improvement in prealbumin levels was associated with improved survival in adult hemodialysis patients (45). Systemic administration of protein in the form of amino acids early in the course of experimental AKI in small animal models of nephrotoxic and septic AKI had antiinflammatory and antiapoptotic effects in the renal tubular epithelium and may reverse AKI (46,47). Adults with oliguric AKI who were given intravenous amino acid infusions have a faster rate of renal recovery and higher survival than patients who were given isocaloric carbohydrates alone (48).…”
Section: Discussionmentioning
confidence: 99%
“…Low serum prealbumin levels, a marker of nutritional status, were correlated with increased mortality in adults with AKI (44), and sustained improvement in prealbumin levels was associated with improved survival in adult hemodialysis patients (45). Systemic administration of protein in the form of amino acids early in the course of experimental AKI in small animal models of nephrotoxic and septic AKI had antiinflammatory and antiapoptotic effects in the renal tubular epithelium and may reverse AKI (46,47). Adults with oliguric AKI who were given intravenous amino acid infusions have a faster rate of renal recovery and higher survival than patients who were given isocaloric carbohydrates alone (48).…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies have shown that Gln improves the antioxidant defenses in patients [3][4][5]127] and attenuates apoptosis in experimental rat [6][7][8]128]. The enterocytes in the small intestine convert the most of Gln in diet and plasma to Ala, Cit and Pro that are released into the blood circulation in Gln-supplementation mammalian [9][10][11][12].…”
Section: Effects Of the Combination Of Ala Cit And Pro On • Oh-inducmentioning
confidence: 99%
“…Studies demonstrated that Gln improves clinical antioxidant outcome in patients [3][4][5] and attenuates apoptosis in experimental rat [6][7][8]. The anti-oxidative and anti-apoptotic effects of Gln may be closely associated with its metabolites in mammalian.…”
Section: Introductionmentioning
confidence: 99%
“…8 Significant progress in understanding the role of apoptosis and its triggering factors has been made in the last decade. Many growth factors (such as hepatocyte growth factor, α-melanocytestimulating hormone, erythropoietin and colony-stimulating-factor-1) [9][10][11][12][13] and drugs (such as glutamine and furosemide) 14,15 have been confirmed to attenuate AKI by inhibiting the apoptosis of renal tubular cells. In contrast, bortezomib and rapamycin aggravated AKI by enhancing tubular cell apoptosis.…”
Section: Introductionmentioning
confidence: 99%